Innovation and gendered negotiations: Insights from six small-scale fishing communities - Locke, Catherine; Muljono, Paramita; McDougall, Cynthia; Morgan, Miranda (Wiley, 2017)
This publication investigates how gender relations shape the capacity and motivation of different individuals in fishing communities to innovate. It compares six fishing communities in Cambodia, the Philippines, and the Solomon Islands. The findings suggest that gendered negotiations mediate the capacity to innovate but that wider structural constraints are important constraints for both men and women. The paper shows that men’s and women’s capacity to innovate is strongly mediated by the behavior of their marriage partner.